PENERAPAN TERAPI SEFT SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH BINAAN PUSKESMAS ROWOSARI SEMARANG: THE APPLICATION OF SEFT SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) THERAPY TOWARDS REDUCING BLOOD PRESSURE IN HYPERTENSION PATIENTS IN THE ESTABLISHED AREA OF ROWOSARI PUSKESMAS SEMARANG - Aprillya Dwi Sarweni; Novita Wulan Sari (JURNAL KEPERAWATAN SISTHANA, 2020)
Hypertension is situation where blood pressure exceeding the limit of normal with blood pressure 140/90 mmHg and which includes non contagious disease. Complementary therapy can reduce the risk of hypertension complications. SEFT therapy one of a complementary therapy that can be used to overcome the problem of increasing blood pressure. The purpose of this study was to carried out SEFT therapy towards decreasing blood pressure in hypertension patients in the built area of Puskesmas Rowosari Semarang. This type of researAch is descriptive using the case study approach method. The criteria used in the case study: primary hypertension patients, hypertension sufferers were able to communicate well, hypertension patients who did not take anti-hypertension drugs. Case study analysis was carried out by processing data through observation of blood pressure before and after SEFT therapy. The results of the case study showed that there was a decrease of blood pressure. Before therapy the blood pressure of the subject I was 170/110 mmHg decreased to 120/80 mmHg and in subject II before therapy, blood pressure 160/100 decreased to 140/80 mmHg. The recommendation is with control of blood pressure by using SEFT therapy, the society can apply this therapy.